2019
DOI: 10.1002/ffj.3522
|View full text |Cite
|
Sign up to set email alerts
|

Composition, and antioxidant and enzyme‐inhibition activities, of essential oils from Satureja thymbra and Thymbra spicata var. spicata

Abstract: This research sought to characterize the essential oils of Satureja thymbra and Thymbra spicata var. spicata in terms of composition as well as their antioxidant and enzyme‐inhibitory activities. The major components of essential oil derived from S. thymbra were found to be γ‐terpinene (34.67%), carvacrol (32.45%), p‐cymene (11.46%), and β‐caryophyllene (6.85%). In the essential oil derived from T. spicata var. spicata the most abundant compounds were carvacrol (63.23%), γ‐terpinene (18.94%), and p‐cymene (8.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 54 publications
0
9
1
Order By: Relevance
“…The observed potential was mainly attributed to the phenolics constituents. Many studies found that phenolic compounds had countless therapeutic activities [ 36 , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] ]. EOs of lavender exhibited antioxidant activity investigated using DPPH, FRAP, and ABTS [ 57 ].The lavender EO resulting in scavenge of 50% of DPPH radical was 51.05 mg/ml [ 58 ] and 16.27 mg/ml (Pistelli) [ 57 ], and 27.7 mg/mL (Blažeković), EC 50 of salvia EOs in DPPH assay was 100 μg/ml [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…The observed potential was mainly attributed to the phenolics constituents. Many studies found that phenolic compounds had countless therapeutic activities [ 36 , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] ]. EOs of lavender exhibited antioxidant activity investigated using DPPH, FRAP, and ABTS [ 57 ].The lavender EO resulting in scavenge of 50% of DPPH radical was 51.05 mg/ml [ 58 ] and 16.27 mg/ml (Pistelli) [ 57 ], and 27.7 mg/mL (Blažeković), EC 50 of salvia EOs in DPPH assay was 100 μg/ml [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…are catalysts of many free radical-generating processes, and certain essential oil phenolics can combine with these transition metals to prevent metal-induced free radical generation ( 23 ). In addition, some active antioxidant substances in plant essential oils can bind to receptors on cells and increase the secretion of antioxidant enzymes through signal transduction, thus enhancing antioxidant defense capacity ( 24 ). Overall, the effects of plant essential oils on free radicals and damaged tissues result in inhibition or delay of aging.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, C. limon (L.) Osbeck essential oil characterized by a composition rich in limonene presented values of antiradical activity comparable to that of the standard [ 41 ]. In a similar way, essential oils with γ-terpinene as one of the main volatile components exhibited appreciable antioxidant and antiradical activity based on several assays including DPPH and ABTS tests [ 42 ]. Reactions of the pure compound with ABTS •+ and DPPH • implied that γ-terpinene was able to directly scavenge radicals as well as protect methyl linoleate, DNA and erythrocytes from oxidation induced by 2,20-azobis (2-amidinopropane hydrochloride) [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, Foti and Ingold [ 44 ] proved an unusual mechanism of inhibition of lipid peroxidation by γ-terpinene via a very fast cross-reaction between HOO • and LOO • radicals. Other terpenoids such as p -cymene and β-pinene were detected as main constituents of some essential oils active against DPPH • or showing different antioxidant abilities [ 42 , 45 , 46 ]. In addition, juices contain a variety of active substances, which could interact and affect the overall antiradical activity.…”
Section: Discussionmentioning
confidence: 99%